Patterns of acute poisoning- Five year study from National Poison Control Centre, Karachi, Pakistan - Ali, Muhammad Ikram; Hassan, Qudsia; Anwar, Azra; Haider, Shahbaz (Journal of the Pakistan Medical Association, 2023)
Objective: To identify patterns in cases of acute toxicity reported at an urban poison control centre. Method: The cross-sectional, retrospective study was conducted at the National Poison Control Centre, Karachi, and comprised data from January 1, 2017, to December 31, 2021. Data was collected from the institutional database which is part of the Jinnah Postgraduate Medical Centre, Karachi. Data of all patients diagnosed with acute poisoning was included. Data was analysed using SPSS 22. Results: Of the 4,936 cases reported, 2,449(49.6%) were males and 2,487(50.3%) were females. Pesticide was the most common cause of toxicity 1254(25.4%). Regarding outcomes, 351(7.1%) patients expired, 3,585(72.6%) were discharged after appropriate treatment, 366(7.4%) were given outpatient and psychiatric referrals, and 634(12.8%) patients left against medical advice. Conclusion: The most common agent causing toxicity was pesticides, and overall mortality across the study period was 7.1%. Key Words: Poisoning, Toxicology, Pesticides, Forensic toxicology.